Loss-based optical trap for on-chip particle analysis - Kühn, S. (2009)
Optical traps have become widespread tools for studying biological objects on the micro and nanoscale. However, conventional laser tweezers and traps rely on bulk optics and are not compatible with current trends in optofluidic miniaturization. Here, we report a new type of particle trap that relies on propagation loss in confined modes in liquid-core optical waveguides to trap particles. Using silica beads and E. coli bacteria, we demonstrate unique key capabilities of this trap. These include single particle trapping with micron-scale accuracy at arbitrary positions over waveguide lengths of several millimeters, definition of multiple independent particle traps in a single waveguide, and combination of optical trapping with single particle fluorescence analysis. The exclusive use of a two-dimensional network of planar waveguides strongly reduces experimental complexity and defines a new paradigm for on-chip particle control and analysis.